Exploring future large-scale ROADM architectures - Morão, D.; Cancela, L.; Rebola, J. (Conftele 2021, 2021)
Most of today’s optical networks are based on reconfigurable optical add/drop multiplexers (ROADMs) nodes. However, current ROADM architectures have poor scalability due to limitations on the wavelength selective switches dimension. Hence, due to the constant increase in data traffic and the demand for more dynamic and flexible networks, current architectures might become a bottleneck in the foreseen large-scale ROADMs. In this work, several architectures for large-scale ROADMs proposed to overcome this bottleneck are studied in terms of hardware cost and in-band crosstalk generation and compared with large-scale ROADMs built with conventional architectures. We show that ROADMs based on a sub-system modular architecture, also known as interconnected architecture, exhibit a significant hardware cost reduction in relation to conventional architectures and are also advantageous regarding the in-band crosstalk generation. Moreover, in this work, an analysis of optical filtering effects, amplified spontaneous emission noise and in-band crosstalk impact in the performance of an optical network, with nodes based on the interconnected architecture, is performed through Monte-Carlo simulation.